Semilinear integro-differential equations with compact semigroups. (1998) - Bahuguna, D.; Srivastava, S. K.
Abstract : In this paper we study the local and global existence of mild solutions to a class of integro-differential equations in an arbitrary Banach space associated with the operators generating compact semigroups on the Banach space.